2014
DOI: 10.1002/ajh.23835
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib‐ and thalidomide‐induced peripheral neuropathy in multiple myeloma: clinical and molecular analyses of a phase 3 study

Abstract: A subanalysis of the GIMEMA-MMY-3006 trial was performed to characterize treatment-emergent peripheral neuropathy (PN) in patients randomized to thalidomide-dexamethasone (TD) or bortezomib-TD (VTD) before and after double autologous transplantation (ASCT) for multiple myeloma (MM). A total of 236 patients randomized to VTD and 238 to TD were stratified according to the emergence of grade 2 PN. Gene expression profiles (GEP) of CD1381 plasma cells were analyzed in 120 VTD-treated patients. The incidence of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…[9][10][11] Peripheral neuropathy, which can be irreversible and may impair the quality of life of a patient, is an important issue when selecting a specific induction regimen, but the analysis of a large Italian trial that investigated VTD induction followed by ASCT showed that PN induced by this triplet combination may resolve in the majority of the cases or may improve to grade 1 in at least 90% of the patients. 17 Overall, in our trial, the rate of severe AEs was identical in both arms, and the number of patients that could not receive the planned schedule of induction was very low. Importantly, .90% of the patients underwent successful stem cell harvest, and VTD induction was associated with a superior stem cell yield as compared with VCD.…”
Section: -11mentioning
confidence: 64%
“…[9][10][11] Peripheral neuropathy, which can be irreversible and may impair the quality of life of a patient, is an important issue when selecting a specific induction regimen, but the analysis of a large Italian trial that investigated VTD induction followed by ASCT showed that PN induced by this triplet combination may resolve in the majority of the cases or may improve to grade 1 in at least 90% of the patients. 17 Overall, in our trial, the rate of severe AEs was identical in both arms, and the number of patients that could not receive the planned schedule of induction was very low. Importantly, .90% of the patients underwent successful stem cell harvest, and VTD induction was associated with a superior stem cell yield as compared with VCD.…”
Section: -11mentioning
confidence: 64%
“…Of the most common grade 3-4 AEs recorded during induction therapy and listed in Table 2, peripheral neuropathy (PN) 7 and skin rash occurred more frequently with VTD compared to VCD(7% vs 2%, p=0.009,and 8% vs 1%, p<0.001, respectively). By the opposite, VCD was associated with a higher probability of severe anemia (7% vs 0%, p=0.003), neutropenia (8% vs 2%, p<0.001) and thrombocytopenia (4% vs <1%, p=0.006) than VTD.…”
mentioning
confidence: 95%
“…[27][28][29] It has been suggested that concomitant cyclophosphamide 30 or IMiD 25 treatment could reduce BiPN; however, reliable evidence is lacking. Whereas some genetic risk factors have been defined, 31,32 clinically useful predictors for BiPN and TiPN are not available, although preexisting PN does heighten the risk. Along this line, our patient may have had subclinical diabetic PN.…”
Section: Comments About Patient 1 Peripheral Neuropathymentioning
confidence: 99%